Distribution and bioaccumulation of trace metals in urban semi-arid mangrove ecosystems - Robin, Sarah Louise; Marchand, Cyril; Mathian, Maximilien; Baudin, François; Alfaro, Andrea C. (Frontiers in Environmental Science, 2022)
Mangrove ecosystems are known to act as filters for contaminants between land and sea. In New Caledonia, urbanization has increased along the coastline during the last decades. However, the impact of urbanization on contaminant cycling in mangrove forests has remained unexplored. In this study, we investigated trace metals (TM) dynamics in an urban mangrove soil and their transfer to mangrove tissues for the two dominant mangrove species in New Caledonia: Avicennia marina and Rhizophora stylosa. The results suggest that decades of urban rainwater runoff from an upper neighborhood induced large variations of mangrove soil physico-chemical properties compared to a control mangrove site sharing the same geological watershed. The urban mangrove site had a neutral pH and low salinity in the upper soil, while the control mangrove site presented acidic pH and a salinity ranging from 24 to 62 g L-1. Most TM were significantly less concentrated in the urban mangrove soil. However, higher root bioconcentration factors (BCF) were measured in the urban mangrove soil compared to the control mangrove soil. For instance, Ni was 15 times less concentrated in the soil and the root BCF was 10 times greater at the urban site. The bioavailability of TM in the urban mangrove soil may be favored by suboxic conditions associated to less Cl-TM complexes and pyrite-TM complexes in the soil. Only Cu, Pb, Ti, and Zn, usually associated with urbanization, were 1.5 to 2 times more concentrated in the urban mangrove soil. No significant difference in translocation factors was measured between the two sites, evidencing a regulation of TM translocation to the upper tissues by mangrove trees.